The effect of exercise on the serum proteomes and metabolomes of elite-level athletes in different sports disciplines - SEO, YOON DAM; KANG, IN SEON; 이현정; Hwang, Ji In; SON, Jung hyun; Oh, Min-Kyu; Min, Ho phil (22nd Human Proteome Organization (HUPO 2023), 2023)
Proteomics and metabolomics are closely interconnected fields that provide valuable insights into the complex mechanisms underlying biological systems. Exercise also exerts its influence on these protein networks. These proteins play a crucial role in metabolic processes, impacting the generation and utilization of metabolites through their expression levels and activities. Consequently, the integration of proteomic and metabolomic data enables a deeper comprehension of biological phenomena, allowing for a comprehensive exploration of molecular interactions and dynamics within organisms. In this study, we have placed our focus on investigating proteomic and metabolomic profiles in the serum of elite-level athletes representing various sports disciplines. For the proteomic analysis, we profiled serum samples using the data-independent acquisition(DIA) method. DIA necessitates the use of a comprehensive spectral library to interpret the more intricate spectra obtained. To develop an in-house library, Initially, serum pools were initially subjected to pre-treatment to construct a data-dependent acquisition (DDA) library. Subsequently, DIA and gas-phase fractionation (GPF)-DIA were utilized for data-independent acquisition analysis, allowing for a comprehensive in-house library for the proteome. consequently, We were able to construct a total of 1257 in-house proteomic libraries using GPF-DIA, DIA, DDA, and the DIA 18 min method, and identified an average of 415 proteins in serum samples from a total of 232 elite athletes. Concurrently, for metabolomic analysis, an in-house library containing approximately 1300 standard substances was established to facilitate metabolite identification in serum samples. Based on this, we conducted metabolome profiling of elite athletes. In this study, we conducted protein profiling and metabolite profiling on serum samples obtained from elite-level athletes. The athletes were divided into four groups: the high-power group, the high-endurance group, the high-endurance group, and the moderate-endurance. We were able to identify differences in proteome and metabolome according to exercise characteristics within the power and endurance groups.Exercise induces systematic changes in the average concentrations of proteins and metabolites related to energy metabolism and various branches of metabolism. These results suggest that elite athletes participating in high and moderate activities exhibit a different metabolic profile.